Post-trial access to medication: an approach based on different knowledge - Schlemper Junior, Bruno Rodolfo; Albuquerque, Aline (O Mundo da Saúde, 2016)
This article approaches clinical trials to test medication in Brazil, and its goal is to analize the issue of post-trial access to drugs that have proven to be beneficial to the research participants from the ethical, sanitary, legal and of the human rights perspectives. In order to do so, a revision was conducted of the main national and international norms, including the normative documents related to human rights and judicial rulings pronounced by the national Courts. It is concluded that there have been important advances in this field, shown by the consensus that the research participants must have total access to the benefits explained in the project and, in Brazil, these benefits are particularly supported by Resolution No 466/2012 of the National Health Council, by the Resolution of the Board of Directors No 38/2013 of the National Health Surveillance Agency and by judicial rulings. Moreover, from the perspective of the human rights, it is established that denying the post-trial drug access represents a violation of the human right to health.